Medicinal plants used in the treatment of neurological disorders by traditional practitioners of YSR Kadapa District, Andhra Pradesh, India - Siddamurthy, Rajagopal Reddy; Araveeti, Madhusudhana Reddy (Ethnobotany Research and Applications, 2026)
Background: The YSR Kadapa District of Andhra Pradesh, India, possesses a rich heritage of ethnomedicinal knowledge, with local communities relying heavily on plant-based remedies for healthcare. Neurological disorders present a significant health burden and traditional plant-based treatments offer a vital, culturally important alternative to conventional medicine. However, this traditional knowledge is vulnerable to erosion due to modernization and environmental degradation. Methods: Ethnobotanical data were collected through interviews and discussions with 75 informants, including traditional healers and local villagers across the district. Information on plant species, local names, families, modes of administration and specific medicinal uses for neurological conditions was meticulously documented and verified. Herbarium specimens were prepared for each species. Results: The present study documented 41 plant species under 39 genera from 39 families used by traditional practitioners to treat 15 different neurological disorders, including epilepsy, Alzheimer’s disease, Parkinson’s disease, migraine, depression etc. The botanical name, local name, habit, family and precise mode of administration for each species are presented. Conclusions: This research underscores the profound ethnomedicinal knowledge within local communities of YSR Kadapa and highlights the critical role of plant biodiversity in regional healthcare. The findings emphasize the urgent need to conserve both this invaluable traditional knowledge and the plant species themselves. Further, pharmacological validation of these plants is essential to integrate these traditional remedies into evidence-based healthcare and ensure their sustainable use for future generations. Keywords: Ethnomedicinal plants, neurological disorders, traditional knowledge, YSR Kadapa District